Orbital magnetization of three-dimensional Dirac electrons in the quantum limit. (7th June 2023) - Kawamura, Shogo; Fuseya, Yuki
Abstract: In this study, we evaluated the dependence of magnetization of three-dimensional Dirac electrons in the quantum limit on the magnetic field and temperature. The magnetization was calculated by differentiating the free energy with respect to the magnetic field. The field and temperature dependence of the chemical potential were entirely considered under the canonical ensemble condition. The total magnetization M consisted of two contributions from the conduction M c and valence M v bands. M v was insensitive to temperature and exhibited sub-linear field dependence, which is consistent with the previous research on Dirac electrons. By contrast, M c was sensitive to both temperature and magnetic field, yielding a non-trivial contribution to the total M . As a result, the properties of total M changed at approximately k B T ≃ E F, where E F is the Fermi energy measured from the band bottom and k B is the Boltzmann constant. At low temperatures k B T ≲ E F, M exhibited sub-linear field dependence, whereas M exhibited super-linear field dependence at high temperatures k B T ≳ E F . This qualitative change in the field dependence of M will play a significant role in the magnetization of Dirac electrons with small E F .